Assessment of Teaching Practice Competency Among in-Service Teacher Degree Program (PPG) in Universiti Tun Hussein Onn Malaysia - Lee, Ming Foong; Lim, Johnson Soon Chong; Lai, & Chee Sern (Journal of Technical Education and Training, 2018)
The best teacher preparation programs emphasise subject matter mastery and provide many opportunities for preservice teachers to spend time in real classrooms under the supervision of an experienced mentor. Thus, teaching practice plays utmost important component of teacher training in order to produce a high quality of future teacher due to the lacking of opportunity or comfort level to work on their pedagogy knowledge while managing their first class. But this condition is slightly different for in-service teacher with diploma and upgrade to degree through the in-service teacher degree programme (PPG) path. PPG is conducted in 4 years using distance learning mode. In-service teachers will attend the courses during weekend and only five times face-to-face meeting with the lecturers. PPG aims to improve the quality of teaching and school management by increasing the teachers’ level of educational qualifications. However, issues were highlighted where teaching competency or performance among in-service teachers are varied during teaching practice observation. Due to their part-time mode of learning, there are concerns whether their performance is at par with their full time peers. Therefore, this paper aims to discuss the assessment of teaching practice competency among the PPG students. This study was applied the Documentation analyses as the research design by using the Teaching Assessment Form of Faculty of Technical & Vocational Education, Universiti Tun Hussein Onn Malaysia. Descriptive statistic using mean and standard deviation were used to analyses the collected data. The result showed that the competency of in-service teachers in teaching practicum in descending order is Personality>Portfolio> Implementation of Teaching> Lesson Planning> Implementation off Innovation> Justification of Innovation>Reflection. Results also showed that in-service teachers are good in affective (M=4.33, SD=0.48), follow by psychomotor (M=4.12, SD=0.47) and cognitive (M=3.99, SD=0.56). In conclusion, in-service teachers need training for innovation in teaching and emphasise in cognitive taxonomy.